Gestão democrática da educação básica: vivências e reflexões teóricas - Ribeiro, Almir (2009)
The objective of this research is to discuss the different dimensions of what constitutes the democratic management of public schools. It seeks to estabilish a reflection about the concept of democracy, considering public politics in the field of education, educational systems, as well as it organization. It also includes a reflection on the concept of autonomy in a historical perspective, with special notes to the “Constituição Federal de 1988 and Lei de Diretrizes e Bases da Educação Nacional”. The qualitative approach of this study presents an analysis on the concepts related to politic action and the effects in the organization of public institutions of education; giving special attention to the rules that also must be followed in a democratic management. Finally, it discuss about limits and possibilities as consequence of democratic management, once autonomy has been practiced in public schools, even facing bureaucracy in the aspect of educational area. It also brings anxiety as a result of the hierarchy of structure, constituted in a distance, through legal attitudes from the governement and its influence on the school environment.